Penanaman Nilai Karakter dan Multikultural dalam Pembelajaran Ilmu Pengetahuan Sosial di SMP Negeri 2 Blora - Nugraha, Arya Sena; Salam, Rudi (Sosiolium: Jurnal Pembelajaran IPS, 2021)
Junior High School 2 Blora is a school with a diversity of students and teachers in the school, ranging from culture, language, religion, social status, gender, ability, age, and race. The purpose of this study was to find out how to instill character and multicultural values ​​in social studies learning and the supporting factors for inculcating character and multicultural values ​​in JHS 2 Blora. This type of research is qualitative research. The results of this study indicate that the cultivation of character and multicultural values ​​can be applied in social studies learning by integrating materials that contain character values ​​and multicultural values ​​in them. Instilling character and multicultural values ​​in social science learning at JHS 2 Blora through teaching and learning activities such as group work, utilizing the environment as a learning resource and using the lecture method. The character values ​​inculcated in social studies learning are taken from the main values ​​in the PPK Movement program and for multicultural values, ​​it is directly guided by the values ​​of tolerance, equality/equality, kinship/brotherhood, unity, and justice. The cultivation of character and multicultural values ​​is supported by the existence of supporting factors in planting, which is carried out in the learning process in the school environment that is directly related to students.